8-(6-6n)+9n=-2+12(n+1)

Simple and best practice solution for 8-(6-6n)+9n=-2+12(n+1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8-(6-6n)+9n=-2+12(n+1) equation:


Simplifying
8 + -1(6 + -6n) + 9n = -2 + 12(n + 1)
8 + (6 * -1 + -6n * -1) + 9n = -2 + 12(n + 1)
8 + (-6 + 6n) + 9n = -2 + 12(n + 1)

Combine like terms: 8 + -6 = 2
2 + 6n + 9n = -2 + 12(n + 1)

Combine like terms: 6n + 9n = 15n
2 + 15n = -2 + 12(n + 1)

Reorder the terms:
2 + 15n = -2 + 12(1 + n)
2 + 15n = -2 + (1 * 12 + n * 12)
2 + 15n = -2 + (12 + 12n)

Combine like terms: -2 + 12 = 10
2 + 15n = 10 + 12n

Solving
2 + 15n = 10 + 12n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-12n' to each side of the equation.
2 + 15n + -12n = 10 + 12n + -12n

Combine like terms: 15n + -12n = 3n
2 + 3n = 10 + 12n + -12n

Combine like terms: 12n + -12n = 0
2 + 3n = 10 + 0
2 + 3n = 10

Add '-2' to each side of the equation.
2 + -2 + 3n = 10 + -2

Combine like terms: 2 + -2 = 0
0 + 3n = 10 + -2
3n = 10 + -2

Combine like terms: 10 + -2 = 8
3n = 8

Divide each side by '3'.
n = 2.666666667

Simplifying
n = 2.666666667

See similar equations:

| (m^2+6m+4)(3m-1)=0 | | 9y^2+2+16=-24y | | 2x+6-x=(3x+18) | | 9y^22+16=-24y | | (w-9)*(w+4)= | | (5x-4)=(4x-7+1) | | =x+3-15+8x | | 7x^3+7x^2+7x+2=0 | | 32x^2-332x+8=0 | | 6x+8=4(x+9) | | 22=t+17 | | 9x+8x-7x-5x=65 | | 3a=a+26+12 | | 2.5s+2.5=7.5 | | 2.5s+2.4=7.5 | | x(2)+40=180 | | 2(2-j)=(j+10) | | 2(1-x)=6 | | 25=2x-y | | 4x+(2x+18)=180 | | 2x^2-4x-3=27 | | 2d=24+6d | | 8+5(z-4)=2(z+7) | | 7(3-x)=14 | | Py+aye=-4y+8 | | 3v-7v=5 | | 3x^2+23x-8.5=0 | | 8v-6v=4 | | 5(4d+8)=80 | | n(17+x)=34x-r | | 14a+20= | | y-5=28 |

Equations solver categories